IMPROVING SMASH ABILITY IN BADMINTON GAMES WITH SHUTTLECOOK THROWING APPROACH FOR GRADE V ELEMENTARY SCHOOL STUDENTS - Munif, Fatkhul Munif (Universitas Muhammadiyah Kuningan, 2025)
The research problem is that learning badminton, which varies with the development of smash skills, cannot be optimally applied to fifth grade students at SD NEGERI Karangwuluh 01, Tegal Regency. This study aims to determine the results of improving smash skills in badminton games for fifth grade students at SD NEGERI Karangwuluh 01 Tegal Regency through the playing approach of throwing shuttlecocks. This research is Classroom Action Research. The research subjects were 32 students in class V. The action research was carried out in two cycles, each cycle with two meetings, each meeting lasting 105 minutes. Data were taken by researchers and collaborators using instruments in the form of observation sheets observing student participation and performance tests of students doing badminton smashes. The results of the student active participation assessment and student performance test results will be analyzed using quantitative descriptive analysis in the form of percentages. While the field notes were processed into meaningful sentences and analyzed descriptively qualitatively, including: data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion, it can be concluded that the action by playing throwing the shuttlecock approach which was carried out in 2 cycles with a total of 4 meetings, was able to improve the ability to smash badminton. This increase includes the learning atmosphere and the development of student badminton smashes. During the learning process, there is an increase in the activeness of student learning, enthusiasm for activity from students, and feelings of pleasure from students in participating in learning activities. In addition, it was also seen that there was an increase in the development of student badminton smashes which were included in the good and very good categories. Keywords: Smash, Badminton, Playing, Throwing Shuttlecook.